2012
DOI: 10.4103/0971-5851.103141
|View full text |Cite
|
Sign up to set email alerts
|

First report of upfront treatment with Gefitinib in comparison with chemotherapy in advanced non-small cell lung cancer patients from south India: Analysis of 120 patients

Abstract: Background:Lung cancer is the most common cause of cancer deaths in males and sixth among females in south India. Lung cancer is being increasingly recognized among non-smokers.Materials and Methods:Stage IIIB and IV advanced non-small cell lung cancer (NSCLC) patients (n=120) treated from January 2009 to December 2010 were retrospectively analyzed. Baseline clinical parameters, treatment protocol, response to therapy and survival were noted. Decision to use upfront Gefitinib was based on parameters like femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In the patients with performance status 2–3, gefitinib led to a significantly longer PFS than chemotherapy (PFS of 10 months vs. 4 months, P = 0.017). [ 51 ]…”
Section: Therapy Of Lung Cancermentioning
confidence: 99%
“…In the patients with performance status 2–3, gefitinib led to a significantly longer PFS than chemotherapy (PFS of 10 months vs. 4 months, P = 0.017). [ 51 ]…”
Section: Therapy Of Lung Cancermentioning
confidence: 99%
“…[34,35] In the study presented by Mehta, EGFR mutation frequency was found to be higher in the Indian population (32%) as compared to Caucasian population; however, it was lower than that reported in the East-Asian population. [36] Median OS (months) Shajeem O et al [9] Chemotherapy combination (38) vs.…”
Section: First-line Treatment With Epidermal Growth Factor Receptor Tmentioning
confidence: 99%
“…[18] This conclusion was adopted fairly across the majority of oncology centers worldwide with Indian studies using pemetrexed-platinum combination showing progression-free survival (PFS) ranging 4-7 months and OS extending to 10 months in epidermal growth factor receptor (EGFR) unmutated cohort of patients in retrospective studies. [19,20] In Phase III randomized trial of East Asians, light/never smokers, unselected for EGFR mutation, and pemetrexed platinum followed by gefitinib maintenance was compared against upfront gefitinib use. This trial failed to show any difference in OS in any of the above groups.…”
mentioning
confidence: 99%
“…The tolerance among Indians was no different. Louis et al [51] reported their experience of first-line use of gefitinib in 47 clinically selected patients from southern India and compared their outcome with 73 patients who were treated with chemotherapy at the same time. They reported a better PFS in the gefitinib group compared to chemotherapy (10 vs. 4 months; p = 0.014) despite the fact that there were more patients with poor PS and higher stage (stage 4) in the gefitinib group.…”
Section: Experience From Indiamentioning
confidence: 99%